Handling Wounds with Nur sing Knowledge at Bhayangkara Hospital Makassar City South Sulawesi - Dunggio, Abdul Rivai Saleh; Djunaedi, Djunaedi; Selvia, Selvia; Syafruddin, Syafruddin; Intang, Nur; Malaha, Naomi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
According to Agency data Center Statistics amount death consequence accident Then cross consequence fracture on in 2020 there were 25,266 people. The most frequent fracture happened in Indonesia is fracture extremities lower. Part frequent body experience fracture that is extremities part lower. Objective Study For know description knowledge nurse to handling terrible emergency patient injured at home Sick Bhayangkara Makassar, South Sulawesi. Design study This use design descriptive is design compiled research like that appearance so that researcher can obtain answer to question study. Design study refers on type or type selected research for reach objective research, as well role as tool and guidelines for reach objective the. Results study that Length of work somebody on something organization or agency No identical with high productivity too. People with period long work no means concerned own level high proficiency. The older a person is working, not yet Of course the more skilled and experienced in his job.